Growing art, displaying relationships : yam technology in Nyamikum Abelam (ESP, PNG) - Coupaye, Ludovic (Material Mediations: People and Things in a World of Movement., 2012)
"How does one make powerful and beautiful and artefacts? What is in certain objects that give them the capacity to act simultaneously as symbols, valuables and images? This book answers these questions through joining together anthropology of material culture, anthropology of art and anthropology of techniques in order to study the decorated long yams of the Abelam of the Sepik in a contemporary Papua New Guinea village. It unpacks their process of making, which requires the combination of agricultural techniques, social interactions, and cosmological knowledge, and provides discussion of the complex positions of study of techniques and arts within anthropology"-